2020
DOI: 10.2460/javma.256.8.906
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical, endoscopic, and histologic features between dogs with chronic gastritis with and without lymphofollicular hyperplasia

Abstract: OBJECTIVE To compare clinical, endoscopic, and histopathologic features between dogs with chronic gastritis (CG) with and without lymphofollicular hyperplasia (LFH). ANIMALS 64 and 56 dogs with CG with (cases) and without (controls) LFH, respectively. PROCEDURES The medical record database of a referral clinic was searched to identify dogs that underwent endoscopic examination of the upper portion of the gastrointestinal tract and were subsequently determined to have CG with or without LFH between October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…According to our experience and a previous study, FBs seemed to be predisposed to GLFH. We believe that this apparent association is circumstantial 5 because we usually evaluate FBs at a young age to evaluate BOAS or because they are experiencing vomiting or regurgitation. In these young dogs, HLO infection is highly prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to our experience and a previous study, FBs seemed to be predisposed to GLFH. We believe that this apparent association is circumstantial 5 because we usually evaluate FBs at a young age to evaluate BOAS or because they are experiencing vomiting or regurgitation. In these young dogs, HLO infection is highly prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the pathophysiology of GLFH in dogs remains unknown. A recent study found an association between young age and GLFH in dogs 5 . In addition, brachycephalic dogs with increased inspiratory effort seem to be overrepresented in the population with GLFH 5‐7 .…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a previous study, there was also an incidence of diarrhoea of 64% in cases with chronic gastritis and lymphofollicular hyperplasia. 7 Chronic lymphoplasmacytic gastritis sometimes responds to dietary therapy alone. If such therapy is inadequate, glucocorticoids can be used concurrently.…”
Section: Discussionmentioning
confidence: 99%